2019
DOI: 10.1016/s2213-8587(19)30086-5
|View full text |Cite
|
Sign up to set email alerts
|

Albuminuria-lowering effect of dapagliflozin alone and in combination with saxagliptin and effect of dapagliflozin and saxagliptin on glycaemic control in patients with type 2 diabetes and chronic kidney disease (DELIGHT): a randomised, double-blind, placebo-controlled trial

Abstract: Current word count-250 words Background: We assessed the effects of the SGLT2 inhibitor dapagliflozin alone and in combination with the DPP4 inhibitor saxagliptin on albuminuria and HbA1c in patients with type 2 diabetes and chronic kidney disease in a double-blind placebo-controlled multicentre multinational study (DELIGHT study; clinicaltrials.gov, NCT02547935). Methods: After a 4-week single-blind placebo lead-in period, 448 participants were randomised (1:1:1; using computer-generated codes) to dapaglifloz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
151
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(159 citation statements)
references
References 34 publications
6
151
0
2
Order By: Relevance
“…The renoprotective benefits of dapagliflozin were observed among patients with a relatively high level of renal function at baseline (mean eGFR, 85 mL/min/1.73 m), indicating a potential role for dapagliflozin in the early prevention of CKD in patients with T2D . The DELIGHT study reported the renoprotective effects of dapagliflozin in patients with T2D and moderate‐to‐severe CKD who were undergoing antihypertensive treatments . Treatment with dapagliflozin for 24 weeks resulted in significant reductions in albuminuria, with a mean change from baseline in urine albumin‐to‐creatinine ratio of −21.0% (95% confidence interval [CI], −34.1 to −5.2; P = .011) and in eGFR, with a mean change from baseline of –2.4 mL/min per 1.73 m (95% CI, −4.2 to −0.5; P = .011) as compared to placebo .…”
Section: Renal Outcomes With Sglt‐2 Inhibitorsmentioning
confidence: 99%
See 2 more Smart Citations
“…The renoprotective benefits of dapagliflozin were observed among patients with a relatively high level of renal function at baseline (mean eGFR, 85 mL/min/1.73 m), indicating a potential role for dapagliflozin in the early prevention of CKD in patients with T2D . The DELIGHT study reported the renoprotective effects of dapagliflozin in patients with T2D and moderate‐to‐severe CKD who were undergoing antihypertensive treatments . Treatment with dapagliflozin for 24 weeks resulted in significant reductions in albuminuria, with a mean change from baseline in urine albumin‐to‐creatinine ratio of −21.0% (95% confidence interval [CI], −34.1 to −5.2; P = .011) and in eGFR, with a mean change from baseline of –2.4 mL/min per 1.73 m (95% CI, −4.2 to −0.5; P = .011) as compared to placebo .…”
Section: Renal Outcomes With Sglt‐2 Inhibitorsmentioning
confidence: 99%
“…Dapagliflozin was associated with a significant reduction in the risk of the composite end point of CV death or hospitalization for heart failure (HF) in patients with T2D and established CVD or CV risk, while significant reductions in the risk of the composite end point of CV death, nonfatal myocardial infarction (MI) or nonfatal stroke were observed with empagliflozin in patients with T2D and established CVD, and with canagliflozin in patients with T2D and established CVD or multiple CV risk factors . Empagliflozin, canagliflozin and dapagliflozin were also associated with a reduction in the risk of hospitalization for HF, as well as a reduction in the risk of kidney disease progression . The American Diabetes Association (ADA) 2019 Standards of Medical Care in Diabetes, the ADA and European Association for the Study of Diabetes 2018 consensus report and the American Association of Clinical Endocrinologists/American College of Endocrinology 2019 consensus report have taken into consideration the CV and renal complications of T2D when providing a revised treatment strategy for T2D, recommending SGLT‐2i therapy with proven CV or renal benefit in patients with established CVD or chronic kidney disease (CKD) with or without CVD .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The DELIGHT study investigated the effect of dapagliflozin (with or without the DPP‐4i saxagliptin) on lowering albuminuria in patients with T2D and moderate‐to‐severe CKD (UACR 30–3500 mg/g and eGFR 25–75 mL/min/1.73 m 2 ) being treated with ACEIs or angiotensin II receptor blockers . Following 24 weeks of treatment, significant mean changes from baseline in UACR were observed with dapagliflozin (−21.0%, 95% CI −34.1 to −5.2) or with dapagliflozin plus saxagliptin (−38.0%, 95% CI −48.2 to −25.8) compared with placebo …”
Section: Benefits Of Sodium–glucose Co‐transporter‐2 Inhibitors In Pamentioning
confidence: 99%
“…The DELIGHT study (N = 448) assessed the albuminurialowering effects of dapagliflozin (with or without the DPP-4i saxagliptin) in patients with T2D and moderate-to-severe chronic kidney disease (CKD) (UACR of 30-3500 mg/g and eGFR of 25-75 mL/min/1.73 m 2 ) who were receiving RAASis [64]. Patients treated with dapagliflozin or with dapagliflozin plus saxagliptin had significant reductions in the UACR over the course of the study, while the UACR remained relatively stable in the placebo group.…”
Section: Effects Of Sglt-2is On CV and Renal Outcomesmentioning
confidence: 99%